Nugget Kelor Sebagai Alternatif Bahan Pangan Di Masa Pandemi Covid - 19 Untuk Balita Stunting Di Desa Selojari - Laily Himawati; Yuwanti (LPPM AN Nuur, 2021)
Background: Stunting is a condition of toddlers who have a length or height that is less when compared to age. This condition is measured by a length or height that is more than minus two standard deviations of the median standard of child growth from WHO. Toddler stunting includes chronic nutritional problems caused by many factors such as socioeconomic conditions, maternal nutrition during pregnancy, pain in babies, and lack of nutritional intake in infants. Stunting toddlers in the future will have difficulty in achieving optimal physical and cognitive development (Kemenkes RI, 2018) Purpose: The purpose of this study is to know the influence of giving moringa nuggets as an alternative to food in the new normal era with increased nutritional status (Height / Age) in Stunting Toddlers in Grobogan Regency Method: Quasi experimental study type of study, Population of all toddlers with Z-Score <-2 SD (TB / U measurement indicator), sampling rule of thumb sampling technique How to collect data is done by measuring the child's weight both in the control group and in the intervention group before the intervention (giving moringa nuggets). Nutritional status is expressed in body weight by age and nutritional status is expressed in the Z score of weight based on age (TB/U) Results: There is no change in nutritional status before and after giving moringa leaf nuggets after 30 days of intervention. Conclusion: More research is needed on the administration of moringa nuggets for 90 days to see an increase in the nutritional status of toddlers